PENGENDALIAN TERPADU VEKTOR CVPD DAN HAMA PENYEBAB BUAH BURIK PADA JERUK SIEM DI KABUPATEN LUWU UTARA - Warda ;; Muh. Asaad (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2008)
Integrated Control of CVPD Vectors and Pests of Citrus Cv. Siem in North Luwu District. The production of citrus plants in South Sulawesi in 2004 decreased sharply (10.60 t/ha) due to the infection of CVPD disease. In the field, the spread of CVPD is faster due to the high population of the vector (D. citri). In addition to the low production, citrus fruit quality in that areas is also very low due to the plague of some pests especially thrips (S. citri). The objective of the assessment is to compare yield of citrus between farmers who implemented the integrated control of D. citri and S. citri and farmers who did not implement the integrated pest control. The Assessment was conducted at Pengkajoang Village, Luwu Utara Regency from January to December 2006 using a pair comparison design consisting of two treatments i.e. (1) Integrated Pest Management (IPM) and (2) Non-IPM. The results of the assessment indicated that the number of the fruit per tree was 72.09 fruits on IPM and 55.80 fruits on non-IPM. The vector population per flush per tree and predator population of Coccinelidae on IPM were 2.95 individuals and 2.10 individuals, whereas those on non-IPM were 3.55 and 0.90 respectively. The number of the fruit infected by thrips, S. citri per tree and the intensity of damage per fruit on IPM were 10.40 fruits and 5.95%, whereas those on non-IPM were 12.25 fruits and 7.88%. Farmers' income on IPM was higher (R/C 1,9) than that on non-IPM (1,5). Key words : Citrus cv. Siem, vector pest, integrated control Produksi jeruk siem di Sulawesi Selatan pada tahun 2004 menurun tajam (10,60 t/ha) disebabakan oleh penyakit CVPD (Citrus Vein Phloem Degeneration). Di lapang, serangan CVPD lebih cepat disebabkan oleh tingginya populasi vektor (Diaphorina citri). Selain produksi, mutu buah jeruk juga sangat rendah karena serangan hama penyebab buah burik khususnya thrips (Scirtothrips citri). Tujuan kajian ini adalah untuk membandingkan produkivitas jeruk siem antara petani yang menerapkan pengendalian terpadu vektor CVPD dan hama buah burik dengan petani yang tidak menerapkan pengendalian hama terpadu. Kajian dilakukan di desa Pengkajoang, Kabupaten Luwu Utara pada bulan Januari hingga Desember 2006, menggunakan rancangan petak berpasangan, dengan dua perlakuan yaitu (1) Pengendalian hama secara terpadu (PHT) dan (2) Pengendalian cara petani (non-PHT). Hasil kajian menunjukkan jumlah buah yang terbentuk adalah 72,09 buah pada perlakuan PHT dan 55,80 buah per pohon pada non-PHT. Populasi D. citri per kumpulan tunas per pohon dan populasi predator dari famili coccinelidae pada perlakuan PHT masing-masing 2,95 ekor dan 2,10 ekor, sementara pada perlakuan non-PHT masing-masing 3,55 ekor dan 0,90 ekor. Jumlah buah terserang hama trips, S. citri per pohon dan intensitas serangan per buah pada perlakuan PHT masing-masing 10,40 buah dan 5,95%, sementara pada perlakuan non-PHT masing-masing 12,25 buah dan 7,88%. Penerimaan petani yang menerapkan PHT lebila tinggi (R/C 1,9) dibanding yang tidak menerapkan PHT (R/C 1,5). Kata kunci : Jeruk Siem, vektor CVPD, hama burik, pengendalian terpadu